PENGARUH LEVERAGE, PROFITABILITY, UKURAN PERUSAHAAN, CAPITAL INTENSITY RATIO, DAN SALES GROWTH TERHADAP TAX AVOIDANCE - Viorent Viorent; Abubakar Arief (STMIK Widuri Jakarta, 2023)
This study aims to determine the effect of leverage, profitability, size firm, capital intensity ratio, and sales growth on tax avoidance in consumer non-cyclicals manufacturing companies listed on Bursa Efek Indonesia in 2019-2022. The type of data in this study is quantitative with secondary data. The sample used in this study was 36 consumer non-cyclicals manufacturing companies with 106 financial statements. The sampling technique uses purposive sampling technique. The analysis methods used in this study are multiple linear regression analysis and descriptive analysis. The results showed that leverage did not have a positive effect on tax avoidance, while Return on Assets (ROA) had a negative effect on tax avoidance, firm size did not have a positive effect on tax avoidance, while Capital Intensity Ratio (CIR) and sales growth did not have negative effect on tax avoidance.